99.0k views
1 vote
Assume a series solution x(t) =summation ^ infinity _ n = 0 a_n t ^n for the equation x" + X = 0. Show that the recursion formula for the coefficients is a_m + 2= -a _m/(m + l1(m + 2), m = 0, 1, 2,... and that this leads to the general solution x (t) = a_0 (1 - t^2/2! + t^4/4! + ...) +a_1 (t - t^3/3! + t^5/5! + ... = a_0 cos(t) + a_1 sin(t)

1 Answer

3 votes

Assume


x=\displaystyle\sum_(n\ge0)a_nt^n


\implies x''=\displaystyle\sum_(n\ge0)(n+1)(n+2)a_(n+2)t^n

Substituting these series into the ODE gives


\displaystyle\sum_(n\ge0)\bigg[(n+1)(n+2)a_(n+2)+a_n\bigg]t^n=0

from which we get


(n+1)(n+2)a_(n+2)+a_n=0\implies a_(n+2)=-(a_n)/((n+1)(n+2))

for
n\ge0, given
x(0)=a_0 and
x'(0)=a_1. Now,

  • if
    n=2k for integer
    k\ge0, then


k=0\implies n=0\implies a_0=a_0


k=1\implies n=2\implies a_2=-(a_0)/(1\cdot2)=(-1)^1(a_0)/(2!)


k=2\implies n=4\implies a_4=-(a_2)/(3\cdot4)=(-1)^2(a_0)/(4!)


k=3\implies n=6\implies a_6=-(a_4)/(5\cdot6)=(-1)^3(a_0)/(6!)

and so on, with the general rule


a_(2k)=(-1)^k(a_0)/((2k)!)

  • and if
    n=2k+1, then


k=0\implies n=1\implies a_1=a_1


k=1\implies n=3\implies a_3=-(a_1)/(2\cdot3)=(-1)^1(a_1)/(3!)


k=2\implies n=5\implies a_5=-(a_3)/(4\cdot5)=(-1)^2(a_1)/(5!)


k=3\implies n=7\implies a_7=-(a_5)/(6\cdot7)=(-1)^3(a_1)/(7!)


\implies a_(2k+1)=(-1)^k(a_1)/((2k+1)!)

So the series solution is


\displaystyle x(t)=\sum_(k\ge0)\bigg(a_(2k)t^(2k)+a_(2k+1)t^(2k+1)\bigg)


x(t)=\displaystyle a_0\sum_(k\ge0)((-1)^kt^(2k))/((2k)!)+a_1\sum_(k\ge0)((-1)^kt^(2k+1))/((2k+1)!)


\implies x(t)=a_0\cot t+a_1\sin t

User Dushan
by
5.3k points